Developing of STEM-Oriented Teaching Materials on Object Motion for Class VIII Junior High Schools - Widi Syahroni, Mohammad; Rusilowati, Ani; Ridlo, Saiful (Journal of Innovative Science Education)
This study aims at developing STEM (Science, Technology, Engineering and Mathematic) oriented teaching materials on The Object Motion, testing the validity and analyzing the readability of the teaching materials that are developed. The method used in this research was Research and Development (R&D). The teaching materials developed in this study are STEM oriented by integrating the elements of science, technology, engineering design, and mathematics in a whole integration on The Object Motion materials. The teaching materials developed were validated by some experts to collect information related to the accuracy of the content and the validity of the teaching materials, and were also tested for their readability. The instrument in this study was a validation sheets to test the validity and a gap-filling test to analyze the readability of the teaching materials using descriptive analysis techniques. This research resulted in (1) STEM-oriented teaching materials having the characteristics of elements of science, technology, engineering and mathematics presented in a complete coherence, (2) the average validation score given by the experts was 85.68% in the very good validation category, and it was emphasized with the results of the Aiken's V test with the acquisition of Aiken's V validation coefficient of 1.14 in the valid category, (3) the acquisition of an average readability score of 85.18% in the category of easy-to-understand teaching materials. Based on these results, STEM-oriented teaching materials on Object Motion are suitable to use in the learning process of Science Courses in class VIII.